Initial Validation of a Brief Attachment Measure in a Sample of High School Students. Issue 3 (13th July 2021) - Yampolskaya, Svetlana; Massey, Oliver Tom; Walker-Egea, Connie
Abstract: Attachment to a caregiver is considered a major component of youth well-being, but currently few measures are available to assess attachment in youths. The purpose of this study was to examine the psychometric properties of the Connection to Caregiver (CtC) instrument, a measure of connection to a caregiver similar to the Inventory of Parent and Peer Attachment (IPPA). The study was driven by a need to assess connection to a caregiver and the appeal of creating a scale from an existing survey that allows a great deal of longitudinal research on already existing data. The psychometric properties of the new measure, which consists of a set of items used in the National Survey of Child and Adolescent Well-Being study, were examined among high school students. Confirmatory factor analysis of the three-factor model showed excellent fit. Concurrent validity of the CtC with the equivalent subscales of the IPPA and convergent validity of each of the scales with the depressive symptoms were good. The results suggest that the CtC instrument is a valid tool for use in research with adolescents.